2021
DOI: 10.1146/annurev-food-070620-025744
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolates in Brassica Vegetables: Characterization and Factors That Influence Distribution, Content, and Intake

Abstract: Glucosinolates (GSLs) are a class of sulfur-containing compounds found predominantly in the genus Brassica of the Brassicaceae family. Certain edible plants in Brassica, known as Brassica vegetables, are among the most commonly consumed vegetables in the world. Over the last three decades, mounting evidence has suggested an inverse association between consumption of Brassica vegetables and the risk of various types of cancer. The biological activities of Brassica vegetables have been largely attributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 123 publications
0
44
0
Order By: Relevance
“…Since baby leaves represent a natural source of bioactive compounds, they could become an important source for the development of the fresh-cut market [5]. Ali et al [9] found different bioactive compounds in Brassicaceae (organosulfuric phytochemicals that have anticarcinogenic activity, and other phytochemicals, with high antioxidant power); the most important compounds are represented by glucosinolates that have several beneficial effects on human health [10]. Green leafy vegetables are excellent source of antioxidants, which act as radical scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…Since baby leaves represent a natural source of bioactive compounds, they could become an important source for the development of the fresh-cut market [5]. Ali et al [9] found different bioactive compounds in Brassicaceae (organosulfuric phytochemicals that have anticarcinogenic activity, and other phytochemicals, with high antioxidant power); the most important compounds are represented by glucosinolates that have several beneficial effects on human health [10]. Green leafy vegetables are excellent source of antioxidants, which act as radical scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…Glucosinolates are a class of steroid glycosides synthesized from glucose and amino acids. These compounds widely occur as secondary metabolites in cruciferous species, especially Arabidopsis and a large number of economically valuable vegetables [ 5 7 ]. Based on the amino acids from which the compounds are derived, GS can be categorized into aliphatic GS, indolic GS, and aromatic GS [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have a similar structure based on a β- d -thioglucose group, a sulfonated oxime group, and a side chain derived from one of the seven protein amino acids. Glucosinolates are synthesized from aliphatic (leucine, isoleucine, valine, methionine, alanine), aromatic (phenylalanine, tyrosine), and indole (tryptophan) amino acids [ 16 ].…”
Section: Resultsmentioning
confidence: 99%